Comparative analysis of software defined network performance and conventional based on latency parameters - Harahap, Raja Pahlevi; Irmayani, Deci; Muti’ah, Rahma (Sinkron : jurnal dan penelitian teknik informatika, 2022)
Software Defined Network (SDN) offers convenience in managing network devices by simply setting the software control plane so as to reduce the complexity of network configuration. However, the ease of management offered is not always accompanied by an increase in network performance when compared to conventional network architectures. This study will perform a performance comparison analysis between networks with SDN architecture (OpenFlow) and conventional architecture. The research methods applied are: topology implementation on Mininet, network simulation and data collection, data analysis, and comparative analysis. Network performance testing is carried out based on latency parameters that are simulated in one subnet using the Mininet emulator. From the results of the latency test, it is found that the average latency on the SDN network is 0.119ms, while the average latency on the conventional network is 0.09588ms. Based on these results, it can be concluded that the network topology that has better performance based on latency parameters is a conventional network topology with an average latency value of 0.09588ms.